Inflation dynamics in a small open-economy model under inflation targeting: Some evidence from Chile - Marco Del Negro; Frank Schorfheide (Federal Reserve Bank of New York, 2008)
This paper estimates a small open-economy dynamic stochastic general equilibrium (DSGE) model, specified along the lines of Galí and Monacelli (2005) and Lubik and Schorfheide (2007), using Chilean data for the full inflation-targeting period of 1999 to 2007. We study the specification of the policy rule followed by the Central Bank of Chile, the dynamic response of inflation to domestic and external shocks, and the change in these dynamics under different policy parameters. We use the DSGE-VAR methodology from our earlier work (2007) to assess the robustness of the conclusion to the presence of model misspecification.
Keywords: C11; C32; E52; F41; 330; Bayesian analysis; small open-economy DSGE models; model misspecification; Inflationsübertragung; Inflation Targeting; Kleines-offenes-Land; Dynamisches Gleichgewicht; Chile